Comparison Photon Exposure and Energy Absorption Buildup Factors of CR-39 and Trivex Optical Lenses - Bilici, Sevim; Bılıcı, Ahmet; Külahcı, Fatih (My University, 2022)
In the present study, Energy Absorption Buildup Factor (EABF) and Exposure Buildup Factors (EBF) of the CR-39 and Trivex optical lenses are calculated by using the Geometric Progression (GP) fitting method based on ANSI/ANS-6.4.3 database. The study analyses comprehensively for different penetration depths within the energy range of 0.015 - 15 MeV up to 40 mfp. The buildup factors are calculated in the examined materials depending on the photon energy that arrives, the penetration depths, and the chemical composition of the material reach at maximum values in the energy region where inconsistent scattering interaction probabilities are intensive. The results show that the CR-39 optical lens had better radiation shielding performance. The suitability of the results is compared with the powerful software tools (EPICS2017 and Phy-X/PSD), which are preferred frequently in the literature to calculate radiation shielding parameters. It is found that the relative changes between the EPICS2017 and Phy-X/PSD software compared with the results of this study are about 8% and 9% for the CR-39 and Trivex optical lens, respectively. This indicates that the results from the study are in good agreement.
Keywords: Trivex Optical lenses; Phy-X/PSD Software; CR-39; EPICS2017 Library; Buildup factors